Exogenous surfactant for lung contusion causing ARDS: A systematic review of clinical and experimental reports - Merkl, Tomáš; Astapenko, David; Štichhauer, Radek; Šafus, Antonín; Dušek, Tomáš; Kotek, Jiří; Řehák, David; Lochman, Petr (The clinical respiratory journal, 2024)
This systematic review aimed to summarize the available data on the treatment of pulmonary contusions with exogenous surfactants, determine whether this treatment benefits patients with severe pulmonary contusions, and evaluate the optimal type of surfactant, method of administration, and drug concentration. Three databases (MEDline, Scopus, and Web of Science) were searched using the following keywords: pulmonary surfactant, surface-active agents, exogenous surfactant, pulmonary contusion, and lung contusion for articles published between 1945 and February 2023, with no language restrictions. Four reviewers independently rated the studies for inclusion, and the other four reviewers resolved conflicts. Of the 100 articles screened, six articles were included in the review. Owing to the limited number of papers on this topic, various types of studies were included (two clinical studies, two experiments, and two case reports). In all the studies, surfactant administration improved the selected ventilation parameters. The most frequently used type of surfactant was Curosurf® in the concentration of 25 mg/kg of ideal body weight. In most studies, the administration of a surfactant by bronchoscopy into the segmental bronchi was the preferable way of administration. In both clinical studies, patients who received surfactants required shorter ventilation times. The administration of exogenous surfactants improved ventilatory parameters and, thus, reduced the need for less aggressive artificial lung ventilation and ventilation days. The animal-derived surfactant Curosurf® seems to be the most suitable substance; however, the ideal concentration remains unclear. The ideal route of administration involves a bronchoscope in the segmental bronchi.
Keywords: Lung Injury; Animals; poškození plic; Respiratory Distress Syndrome; Contusions; Pulmonary Surfactants; lidé; umělé dýchání; zvířata; bronchoskopie; zhmoždění; syndrom dechové tísně; Respiration, Artificial; Bronchoscopy; Treatment Outcome; plicní surfaktanty; výsledek terapie; Humans